Phospholipase A2 inhibitors as potential therapeutic agents for the treatment of inflammatory diseases - Magrioti, V.; Kokotos, G. (Expert Opinion on Therapeutic Patents, 2010)
Importance of the field: The various phospholipase A2 (PLA2) types have been implicated in diverse kinds of lipid signaling and inflammatory diseases. Rheumatoid arthritis, lung inflammation, neurological disorders, such as multiple sclerosis, cardiovascular diseases, including atherosclerosis, and cancer are included among the diseases where PLA2 enzymes are involved. Thus, there is a great interest in developing potent and selective PLA2 inhibitors and some of them have entered clinical trials. Areas covered in this review: This review article discusses the role of each PLA2 class in inflammatory diseases and the advances in the development of inhibitors presented in patent literature from January 2004 to May 2009. What the reader will gain: PLA2s cluster in four main types: secreted sPLA2, cytosolic cPLA2, Ca2+-independent iPLA2 and lipoprotein-associated LpPLA2. Each of those types has been implicated in diverse kinds of inflammatory diseases. Readers will rapidly gain an overview of the various PLA2 inhibitors reported in the patent literature in the past 5 years. Furthermore, the readers will learn the difficulties related to the development of PLA2 inhibitors as new drugs and also the different companies and research groups that are the main players in the field. Take home message: Although the role of each PLA2 is not yet distinct in different diseases, the development and future use of different PLA2 inhibitors to treat human disease seems very promising.
Keywords: Arthritis; Atherosclerosis; Inflammation; Inhibitors; Multiple sclerosis; Phospholipase A2